Open Globe Injury in Hospital Serdang - An 8-year Retrospective Review - Nazri Omar; Maimunah Abdul Muna'aim; Rozita Ismail; Rafidah Md. Saleh (Universiti Putra Malaysia (UPM), 2024)
Indexed by Scopus